Analisis Implementasi Aplikasi Srikandi dalam Tata Kelola Arsip Digital pada Bidang Bina Marga Dinas PUPR Provinsi Jambi - Siti Nurhalizah Hutagalung; Shofia Amin; Feny Tialonawarmi (EBISMAN eBisnis Manajemen, 2026)
This study aims to examine the implementation of the Integrated Dynamic Archival Information Sistem (SRIKANDI) application in digital archive management at the Public Works and Public Housing Agency (PUPR) of Jambi Province. This study applies a qualitative approach using descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, and documentation of informants directly involved in archive management and the use of the SRIKANDI application. The analysis of policy implementation in this study is based on Edward III's theory, which covers the dimensions of communication, resources, disposition, and bureaucratic structure. The findings of the study show that the implementation of the SRIKANDI application in the Road Construction Division has been carried out, but it has not been running optimally. The use of the application is still mostly focused on correspondence activities, while the comprehensive archive management function has not been optimally implemented. Factors supporting implementation include the existence of clear regulations, leadership commitment, and the availability of socialization and training activities. Meanwhile, the obstacles found include limitations in internet network quality, application stability, and differences in the level of human resource capabilities and adaptation to digital sistems. This study concludes that the successful implementation of SRIKANDI is not only influenced by the availability of technology, but also by the readiness of organizations and human resources in supporting the transformation of digital archive management. In addition, this study also provides several strategic recommendations to improve the effectiveness of implementation.